1998
DOI: 10.1093/humrep/13.10.2751
|View full text |Cite
|
Sign up to set email alerts
|

Hysteroscopic metroplasty in diethylstilboestrol-exposed and hypoplastic uterus: a report on 24 cases

Abstract: The aim of this study was to determine the feasibility and safety of hysteroscopic metroplasty in cases of diethylstilboestrol-exposed and hypoplastic malformed uterus. Twenty-four patients were referred for primary infertility (n = 9), secondary infertility (n = 1) or infecundity (n = 14). Fifteen had been exposed to diethylstilboestrol in utero. All patients had a hypoplastic uterus and/or uterine deformity as seen by hysterosalpingography and each served as their own control. All patients underwent hysteros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 9 publications
6
28
0
2
Order By: Relevance
“…Many of the defects are amendable to therapy and they usually have good outcomes; pregnancy rates have been reported from 63% to 87.5% [7,12,15]. Rates of pregnancy after hysteroscopic metroplasty in septated uterus [2], hypoplastic uterus, diethylstilbestrol-exposed uterus [5], or hysteroscopic lysis of intrauterine adhesions are reported to be high, with an 87% pregnancy rate postoperatively [5,12,13]. Some studies have suggested that hysteroscopic metroplasty with the Nd-YAG laser is a valuable new alternative technique for structural uterine defects (SUD) [3,4].…”
mentioning
confidence: 99%
“…Many of the defects are amendable to therapy and they usually have good outcomes; pregnancy rates have been reported from 63% to 87.5% [7,12,15]. Rates of pregnancy after hysteroscopic metroplasty in septated uterus [2], hypoplastic uterus, diethylstilbestrol-exposed uterus [5], or hysteroscopic lysis of intrauterine adhesions are reported to be high, with an 87% pregnancy rate postoperatively [5,12,13]. Some studies have suggested that hysteroscopic metroplasty with the Nd-YAG laser is a valuable new alternative technique for structural uterine defects (SUD) [3,4].…”
mentioning
confidence: 99%
“…When present, 60% was related to a hypoplastic ''T''-shaped uterine cavity. A lateral metroplasty (34) was performed in these patients. The surgical correction of the additional female pathology in 31% of the patients will definitely have a positive effect on pregnancy rates and/or outcome.…”
Section: Discussionmentioning
confidence: 99%
“…50 Although authors reporting on small series recount positive impressions about the impact of surgery on subsequent reproductive outcome, 51 the efficacy of these procedures remains to be rigorously evaluated.…”
Section: Anatomy and Morphological Measurementsmentioning
confidence: 99%